Excellent Outcome Following Sibling Peripheral Blood Hematopoietic Stem Cell Transplantation for Glanzmann Thrombasthenia: A Case Report - Li, Jian hua; Sun, Shu wen; Ai, Yuan; Yang, Xue; Zhu, Yi ping (Frontiers in Pediatrics, 2022)
Abstract GT is a rare autosomal recessive platelet disorder due to A qualitative or quantitative anomaly of platelet membrane glycoprotein GPIIb/IIIa. Patients with mild to severe bleeding, purpura, epistaxis, gingival bleeding are common, severe bleeding can be life-threatening. Platelet function analysis, flow cytometry and genetic testing are the main methods for laboratory diagnosis. The therapeutics includes local haemostatic procedures, antifibrinolytic drugs, recombinant human activated factor VII and platelet transfusion. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only definitive therapy method for GT. Herein, we report an 2-year boy with severe GT successfully treated with HSCT from his HLA-identical sibling.